EFFECTS OF VIBRATION CONDITIONS ON MACHINABILITY OF AISI 52100 BEARING STEEL - Agar, Salih; Tosun, Nihat; Mahmat, Aybars (World Scientific Publ Co Pte Ltd, 2024)
This study focused on determining the effects of the cooling condition in the conventional and ultrasonic-assisted turning of AISI 52100 steel. AISI 52100 steel has been widely used in the bearing, mold, and automotive industries because of its superior wear resistance and mechanical properties. However, its high wear resistance caused poor machinability in conventional machining methods. Low surface quality, rapid tool wear, high cutting temperature, and high cutting force are the main difficulties in the conventional machining of AISI 52100 steel. On the other hand, ultrasonic-assisted machining has become widely used in the past decades for the machining of materials that have low machinability in conventional methods. Conventional turning and ultrasonic-assisted turning were selected as machining methods. Ultrasonic-assisted turning experiments were conducted under 20 and 30 kHz vibration frequencies. Cubic Boron Nitride (CBN) cutting tools were used in machining experiments. In machining operations 50, 100, and 150 m/min cutting speeds were selected, and feed rate (0.1 mm/rev) and depth of cut (0.5 mm) were kept constant in experiments. Minimum quantity lubrication technique which used 1% Al2O3 nanoparticle additives cutting fluid and dry cooling methods were used. CBN insert was used as a cutting tool. The effects of cutting speed, cutting method, and cooling condition on surface quality, cutting force, cutting zone temperature, and cutting tool wear were studied experimentally. Analysis of Variance (ANOVA) was carried out to determine the significance of the effects of input variables on process outputs. As a result of this study, it is determined that combined UAT and nanoMQL have significant effects on the process outputs.
Keywords: Ultrasonic-assisted turning; surface quality; cutting force; cutting temperature; cutting tool wear; variance analysis